Effects of moderate- and high- intensity warm-up on exercise performance and psychophysiological responses during self-paced interval running - Pauzi, Muhammad Syamil Mohd (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
A high-intensity warm-up can reduce exercise performance and induce negative feelings during exercise, even when perceived exertion and physiological stress are high in adults. The impact of different warm-up intensities on exercise performance and psychophysiological reactions, on the other hand, remains unclear. This study examined the acute affective, perceived exertion and cardiorespiratory responses to self-paced interval running with different warm-up intensities in adults. Warm-up conditions included high intensity warm-up (90% of maximal aerobic speed (MAS)), moderate intensity warm-up (50% of MAS), and no warm-up followed by 5 x 1-minute self-paced interval running separated by 75 seconds recovery on separate days for participants (n = 12; 7 men, 5 women; age 23.0 ± 1.1years). Affective responses, heart rate (HR) and rating of perceived exertion (RPE) were recorded before and after warm-ups and before, during and after self-paced interval running. During the warm-up and work intervals 1 to 5, affective response decreased in all circumstances (p < 0.05), although high intensity warm-up evoked substantially less affective response than moderate intensity and no warm-up. RPE was significantly higher during high intensity warm-up than moderate intensity and no warm-up condition during warm-up and work intervals 1 to 5 (all P < 0.05, ES > 0.6). During the high-intensity warm-up, the majority of the participants reached 90% HRmax, but not during the moderate-intensity warm-up or no warm-up. HR in control condition was significantly lower than high intensity and moderate intensity condition at work intervals 1 and 2, but starting from work intervals 3 to 5, the HR of all warm-up conditions had no significant difference. Despite the fact that exercise performance improved for all intervals under all three warm-up conditions, the pleasant impact experienced during self-paced running after moderate intensity and no warm-up could be used as an approach to motivate adults to start and stick to an exercise regimen.